2016
DOI: 10.1007/s00428-016-2018-6
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland hybrid tumour revisited: could they represent high-grade transformation in a low-grade neoplasm?

Abstract: Salivary gland hybrid tumour, first described in 1996, is a very rare neoplasm for which exact morphological criteria have not been universally agreed upon. In contrast, the concept of high-grade transformation (HGT) in salivary neoplasms has been widely accepted during the last decade, and the number of reported cases is rapidly increasing. A review of the literature revealed 38 cases of hybrid tumour reported in 22 publications. During approximately the same time period, well over 100 cases of HGT in salivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…Genetic analyses of the tumor components that may provide useful information regarding tumorigenesis are even more limited [4, 9]. When encountering such cases, several important differential diagnoses arise regarding the potential relationship and pathogenesis of the tumor components, including hybrid tumor, collision tumor, and malignant transformation or high-grade transformation [2, 4, 10]. A hybrid salivary gland tumor has been defined as the coexistence of two distinct salivary gland tumor entities originating within the same topographical area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses of the tumor components that may provide useful information regarding tumorigenesis are even more limited [4, 9]. When encountering such cases, several important differential diagnoses arise regarding the potential relationship and pathogenesis of the tumor components, including hybrid tumor, collision tumor, and malignant transformation or high-grade transformation [2, 4, 10]. A hybrid salivary gland tumor has been defined as the coexistence of two distinct salivary gland tumor entities originating within the same topographical area.…”
Section: Discussionmentioning
confidence: 99%
“…A hybrid salivary gland tumor has been defined as the coexistence of two distinct salivary gland tumor entities originating within the same topographical area. In contrast, a collision tumor refers to a meeting of two malignant neoplasms that arise at independent topographical sites but subsequently grow into and invade each other; this terminology has most frequently been used to describe tumors of distinct histogenesis (i.e., carcinoma and lymphoma) [4, 11]. Malignant transformation is the process whereby a benign neoplasm undergoes biologic transformation to a malignant neoplasm, most commonly manifested as carcinoma ex pleomorphic adenoma in the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…A gradual transitional area between the high-and low-grade components suggested HGT/dedifferentiation from lowgrade ACC to myoepithelial carcinoma, rather than a hybrid tumor, although the exact definition of a hybrid tumor is considered controversial. 8 Although approximately 40 cases of ACC with HGT/ dedifferentiation have been described since the first case report by Cheuk et al in 1999, 9 only five cases of ACC with myoepithelial dedifferentiation, including our case, have been described in the English literature ( Table 2). The present case is the second example of ACC with HGT/ dedifferentiation to myoepithelial carcinoma, and is the first example to occur in a salivary gland of the epipharynx ( Table 2).…”
Section: Discussionmentioning
confidence: 68%
“…The low‐grade component was conventional, cribriform‐type ACC and the high‐grade component demonstrated sarcomatoid features, with positive immunostaining for calponin, α‐SMA, p63 which were consistent with myoepithelial carcinoma. A gradual transitional area between the high‐ and low‐grade components suggested HGT/dedifferentiation from low‐grade ACC to myoepithelial carcinoma, rather than a hybrid tumor, although the exact definition of a hybrid tumor is considered controversial …”
Section: Discussionmentioning
confidence: 96%
“…Several findings indicated that very likely the mechanism had been a highgrade transformation rather than two different tumours occurring at the same place (still to be separated from so-called collision tumours). During the same period of time (1996-2016) more than a hundred cases of HGT in salivary gland neoplasms had been reported [2]. In another study, we investigated the clinical consequences of HGT in salivary adenoid cystic carcinoma.…”
Section: Commentarymentioning
confidence: 99%